2013
DOI: 10.1210/jc.2012-4280
|View full text |Cite
|
Sign up to set email alerts
|

How Changes in Affinity of Corticosteroid-binding Globulin Modulate Free Cortisol Concentration

Abstract: Context:Recent studies of corticosteroid-binding globulin (CBG) indicate that it does not merely transport cortisol passively but also actively regulates its release in the circulation. We show how CBG binding affinity can vary to give changes in free cortisol concentration in a physiologically relevant range.Objective:The objective was to determine how the binding affinity of plasma CBG is affected by glycosylation, changes in body temperature, and the conformational change induced by proteases at sites of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
86
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 36 publications
4
86
1
1
Order By: Relevance
“…On the other hand similar half-lives would likely compromise enzyme mediated cortisol available for release from CBG. Importantly however, in addition to its transport role, CBG also has a buffering role in stabilizing free cortisol concentrations which is dependent on the binding affinity of intact CBG as well as the much reduced binding affinity of cleaved CBG [11,12]. Hence in conditions where there is a relative high concentration of cleaved CBG knowledge of relative half-lives assumes importance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand similar half-lives would likely compromise enzyme mediated cortisol available for release from CBG. Importantly however, in addition to its transport role, CBG also has a buffering role in stabilizing free cortisol concentrations which is dependent on the binding affinity of intact CBG as well as the much reduced binding affinity of cleaved CBG [11,12]. Hence in conditions where there is a relative high concentration of cleaved CBG knowledge of relative half-lives assumes importance.…”
Section: Introductionmentioning
confidence: 99%
“…Only free cortisol can cross the cell membrane to exert its function by binding to the GR and consequently binding as a complex in the nucleus. The acute response to critical illness comprises an immediate fall in the circulating levels of the binding proteins, CBG and albumin, together with an altered CBGbinding affinity, which occurs via the cleavage of CBG at the sites of inflammation or in the circulation evoked by fever (17,18,19,20,21). Plasma free cortisol has been suggested by other authors to be more appropriate than total plasma cortisol for the assessment of the HPA-axis functioning .…”
Section: Rai In Critical Illnessmentioning
confidence: 99%
“…glycosylated CBG was found to bind cortisol with significantly higher affinity and was more temperature-sensitive relative to nonglycosylated CBG) (29). Moreover, upon NE-based RCL cleavage, the cortisol affinity of glycosylated CBG was reduced more than non-glycosylated forms, indicating that CBG glycosylation may yield a more rapid surge of free cortisol at target tissues to thereby facilitate a quicker resolution of inflammation (29). Intriguingly, the C-terminally located Asn 347 , which is 84.7% occupied by primarily triantennary sialoglycans, is located on the RCL in close proximity to the reported cleavage sites (36).…”
mentioning
confidence: 99%
“…Readers are directed to a recent review as a source of more in depth coverage of the CBG biology (28 to form two complementary fragments: the large (50 -55 kDa) N-terminal fragment (CBG-Nt) and the small (5-10 kDa) C-terminal fragment (CBG-Ct) (22). The reduced cortisol affinity of cleaved CBG increases the local concentration of free cortisol, which is beneficial toward resolving inflammation in affected tissues by the anti-inflammatory effects of cortisol (17,29). It was recently suggested that in basal, low inflammatory conditions, proteases other than NE may be causing systemic CBG cleavage (30).…”
mentioning
confidence: 99%
See 1 more Smart Citation